Adsorptive performance of MOF nanocomposite for methylene blue and malachite green dyes: Kinetics, isotherm and mechanism. (1st October 2018) - Alqadami, Ayoub Abdullah; Naushad, Mu.; Alothman, Z.A.; Ahamad, Tansir
Abstract: In the present study, Fe3 O4 @AMCA-MIL-53(Al) nanocomposite was utilized for the adsorptive removal of highly toxic MB and MG dyes from aqueous environment. The batch adsorption tests were performed at different contact time, pH, Fe3 O4 @AMCA-MIL-53(Al) dose, initial concentration of dyes and temperature. The maximum adsorption capacity of MB and MG dyes onto of Fe3 O4 @AMCA-MIL-53(Al) using Langmuir equation was 1.02 and 0.90 m mol/g, respectively. The isotherm and kinetic studies revealed that adsorption data were well fitted to Langmuir isotherm and pseudo-first-order kinetics models. Various thermodynamic parameters were also calculated and interpreted. The positive and negative values of ΔH° and ΔG° indicated that the adsorption was endothermic and spontaneous, respectively. The adsorptive binding of MB and MG on Fe3 O4 @AMCA-MIL53(Al) nanocomposite was directed by carboxylate and amide groups through electrostatic interaction, π−π interaction and hydrogen bonding. The desorption of both dyes from Fe3 O4 @AMCA-MIL-53(Al) was also performed using mixed solution of 0.01 M HCl/ethanol. Thus, we conclude that the Fe3 O4 @AMCA-MIL-53(Al) was an outstanding material for the removal of dyes from aqueous environment. Graphical abstract: Highlights: Fe3 O4 @AMCA-MIL-53(Al) was used for the removal MB and MG dyes from aqueous medium. The overall removal of MB and MG dyes (25 mg/L) from water reached more than 88%. Adsorption capacity was increased with increase in temperature. Maximum adsorption capacity was higher than those of most reported adsorbents.